2000
DOI: 10.21273/horttech.10.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Floral and Foliage Displays on Human Emotions

Abstract: Changes in human emotions were investigated during exposure to three different indoor conditions: floral display present, foliage display present, and no display present. There were 20 subjects (10 males and 10 females) in each condition. The subjects were shown a video that introduced the University of Reading and included scenes of landscapes. It was shown that a floral display had positive effects on human emotions, such as composition and confidence, however, some evidence of a significant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 8 publications
2
46
0
5
Order By: Relevance
“…[13][14][15][16] Therefore, these three basic factors of plants were chosen in current research. The three features of plants (colour, odour and size), which formed the independent variables in the present research, were inspected.…”
Section: The Experimental Plantsmentioning
confidence: 99%
“…[13][14][15][16] Therefore, these three basic factors of plants were chosen in current research. The three features of plants (colour, odour and size), which formed the independent variables in the present research, were inspected.…”
Section: The Experimental Plantsmentioning
confidence: 99%
“…Due to these beneficial effects, horticultural activity has often been used in rehabilitation programs for patients with different types of disorder [9,10]. It has also been reported that flower decoration, one such typical horticultural activity, can ease negative feelings and enhance cognitive ability [11]. Despite many studies on this subject, little scientific evidence is available on the physiological effects of horticultural activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although we cannot at this time explain the exact nature of this preference, there may be some evidence of this process at work within the research on indoor plants as well. For example, floral arrangements tend to be rated as more attractive than foliage plants (Adachi et al, 2000; see also review Bringslimark et al, 2009). The growth of a foliage plant would not likely be discernible over a short period of time.…”
Section: Nature Exposure and Indoor Plantsmentioning
confidence: 99%
“…Furthermore, flowers often signal the future presence of various fruits, vegetables, and honey. While watching a non-nature related video, participants were exposed to either foliage plants or flowering plants (Adachi et al, 2000). Participants in the flowering plant condition rated the room as more attractive than those in the foliage plant condition.…”
Section: Nature Exposure and Indoor Plantsmentioning
confidence: 99%
See 1 more Smart Citation